Space‐Weathered Anorthosite as Spectral D‐Type Material on the Martian Satellites - S. Yamamoto; S. Watanabe; T. Matsunaga (Geophysical Research Letters)
Abstract Spectral D‐type asteroids are characterized by dark, red‐sloped, and featureless spectra at visible and near‐infrared wavelengths and are thought to be composed of rocks rich in organic compounds. The Martian satellites, Phobos and Deimos, spectrally resemble D‐type asteroids, suggesting that they are captured D‐type asteroids from outside the Martian system. Here we show that the spectral features of lunar space‐weathered anorthosite are consistent with D‐type spectra, including those of Phobos and Deimos. This can also explain the distinct spectral features on Phobos, the red and blue units, as arising from different degrees of space weathering. Thus, D‐type spectra of the Martian satellites can be explained by space‐weathered anorthosite, indicating that D‐type spectra do not necessarily support the existence of organic compounds, which would be strong evidence for the capture scenario.